Evaluation of the effect of Levofloxacin and Cefalexin derivative antibiotics on Implant Osseointegration in rat tibia - Can, Umit Koray; Tanrisever, Murat; Dagtekin, Burak; Pak, Pinar; Ozcan, Erhan Cahit; Istek, Ozmen; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Osseointegration refers to the process where an implant firmly and functionally bonds with the bone, establishing a stable union capable of bearing loads without any relative movement between the implant and the surrounding bone tissue. Post-surgery Infections that may develop in the surgical area can negatively affect osseointegration, putting the success of the implant at risk. The objective of this research was to evaluate the impact of antibiotics derived from levofloxacin and cephalexin on the osseointegration of implants in the tibias of rats. A total of 21 female Sprague Dawley rats were utilized, randomly divided into three equal groups of seven rats each. Titanium implants measuring 2.5 mm in diameter and 4 mm in length were inserted into cavities created in the corticocancellous bone of the metaphyseal region of the right tibias of all animals. In the implant control group (n = 7) no additional procedures were performed throughout the two-week experimental period. Subjects in the implant levofloxacin group (eta = 7) received subcutaneous injections of levofloxacin at a dose 25 mg/kg, administered three times weekly for weeks. Similarly, rats in the implant cephalexin group (n = 7) were given subcutaneous injections of cephalexin at a dosage of 20 mg/kg, three times per week for two weeks. Two weeks after the operation, the implant samples in the tibias of the rats were subjected to biomechanical analysis using a digital torque device in order to evaluate the osseointegration process. As a result, it was observed that levofloxacin and cephalexin-derived antibiotics had a negative effect on implant osseointegration in the tibias of rats.
Evaluación del efecto de los antibióticos derivados de levofloxacino y cefalexina sobre la osteointegración de implantes en tibia de rata
Keywords: Levofloxacin; Cephalexin; osseointegration; rat